2016
DOI: 10.1007/978-3-319-32933-8_1
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Outcomes of Horizontal and Vertical Integration of Sustainability Content into Engineering Curricula Using Concept Maps

Abstract: The goal of this project was to compare the conceptual sustainability knowledge of students at two institutions that differ in their approaches of integrating sustainability into curricula. One institution is a research-intensive university that has implemented a sustainability-focused course (vertical integration), and the second is a teaching-focused university that has woven sustainability into a variety of classes across its curriculum (horizontal integration). At both institutions, students beginning thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…5 The rubric includes two four-point rating scales to aid evaluators in judging capstone reports based on the 16 sustainable design criteria. The earned points scale [0][1][2][3] captures the extent to which students consider each sustainable design criterion in their capstone projects. Evaluators assign a score of 0 to projects that show no evidence of incorporating the design criterion, while a score of 3 is assigned if the project shows evidence of extensive criterion application.…”
Section: Pilot Development and Application Of A Sustainable Design Rumentioning
confidence: 99%
See 3 more Smart Citations
“…5 The rubric includes two four-point rating scales to aid evaluators in judging capstone reports based on the 16 sustainable design criteria. The earned points scale [0][1][2][3] captures the extent to which students consider each sustainable design criterion in their capstone projects. Evaluators assign a score of 0 to projects that show no evidence of incorporating the design criterion, while a score of 3 is assigned if the project shows evidence of extensive criterion application.…”
Section: Pilot Development and Application Of A Sustainable Design Rumentioning
confidence: 99%
“…Evaluators assign a score of 0 to projects that show no evidence of incorporating the design criterion, while a score of 3 is assigned if the project shows evidence of extensive criterion application. The potential points scale [0][1][2][3] describes the extent to which each sustainable design criterion is applicable to a given capstone project. Evaluators assign a score of 0 if the criterion is not applicable to the project.…”
Section: Pilot Development and Application Of A Sustainable Design Rumentioning
confidence: 99%
See 2 more Smart Citations
“…8 More specifically, concept maps have been previously used to evaluate student knowledge of sustainability and related ideas. 2,9,10,20,[44][45][46][47] Segalas et al 34 found that "courses that apply a more community-oriented and constructive, active learning pedagogical approach, increase students' knowledge of [sustainable development]." p. 275…”
Section: Introductionmentioning
confidence: 99%